NAIRAS Version 3 Atmospheric Ionizing Radiation Validation: Comparisons to RaD‐X Measurements - Christopher J. Mertens; Guillaume P. Gronoff; Daniel B. Phoenix (Space Weather)
Abstract The Nowcast of Aerospace Ionizing RAdiation System (NAIRAS) model predicts dosimetric and radiative flux quantities for assessing human radiation exposure levels and radiation effects on flight electronic systems from the surface of the Earth to deep space. NAIRAS version 3 includes many updates and improvements to the model. In this paper, NAIRAS version 3 dosimetric quantities are compared to observations of the atmospheric radiation environment taken during the Radiation Dosimetry Experiment (RaD‐X) flight campaign. The RaD‐X campaign consisted of a high‐altitude balloon flight, with altitudes up to 40 km, and four coordinated aircraft flights covering an altitude range from 6 to 20 km. The RaD‐X measurement data from the different flight platforms were acquired in September 2015 and at nearly the same vertical cutoff rigidity (3–4 GV). High quality, flight‐averaged measurement data were provided at seven altitudes, which correspond to regions of fundamentally different radiation transport and collisional interaction physics. The NAIRAS model agrees with the RaD‐X measurements to within 30% over the entire altitude domain of the flight campaign (0–40 km), which is within the measurement uncertainty.